Characterization and Development of Microsatellite Markers in Pseudotaxus chienii (Taxaceae) Based on Transcriptome Sequencing - Xu, Ruixiang; Wang, Zhen; Su, Yingjuan; Wang, Ting (Frontiers in Genetics, 2020)
Pseudotaxus chienii (Taxaceae) is an endangered conifer species endemic to China. However, a lack of suitable molecular markers hinders the genomic and genetic studies on this species. Here, we characterized and developed the microsatellite markers from a newly-sequenced P. chienii transcriptome. A total of 21,835 microsatellite loci were detected from 161,131 non-redundant unigene sequences, and the frequency of SSRs was 13.55%, with an average of one SSR loci per 9.18 kb. Mono-nucleotide, di-nucleotide, and tri-nucleotide were the dominant repeat types, accounting for 50.06%, 13.49%, and 29.39% of the total SSRs, respectively. In terms of distribution location, the coding regions (CDS) with few microsatellites and mainly consisted of tri-nucleotides. There were significant differences in the length of microsatellite among genic regions and motif types. Functional annotation showed that the unigenes containing microsatellites had a wide range of biological functions, most of which were related to basic metabolism, and a few might be involved in expression regulation of gene and response to environmental stress. In addition, 375 primer pairs were randomly selected and synthesized for the amplification and validation of microsatellite markers. Seventy-seven primer pairs were successfully amplified and 40 primer pairs were found to be polymorphic. Finally, 20 pairs of primers with high polymorphism were selected to assess the genetic diversity in four P. chienii populations. In addition, the newly developed microsatellite markers exhibited high transferability (70%) in Amentotaxus argotaenia. Our study could enable further genetic diversity analysis and functional gene mining on Taxaceae.